2013
DOI: 10.1292/jvms.12-0435
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of <i>Cryptosporidium</i> Isolates from Calves in Ishikari District, Hokkaido, Japan

Abstract: ABSTRACT. Cattle are major hosts of Cryptosporidium. Cryptosporidiosis in neonatal calves is associated with retarded growth, weight loss and calf mortality, and zoonotic infections in humans. Fecal samples were collected from calves in Ishikari District, Hokkaido, Japan and examined by PCR and sequence analyses. Among the 107 fecal samples collected in May and June 2012, 25 (23%) were positive for Cryptosporidium, including 8 samples (7%) having C. parvum, 10 (9%) having C. bovis and 7 (7%) having C. ryanae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This is in agreement with previous studies showing that neonatal calves are highly susceptible to Cryptosporidium infections because of their immature immune system and high exposure to manure or equipment contaminated with oocysts of the parasite (e.g. Foster and Smith, 2009;Murakoshi et al, 2013;Björkman et al, 2015). A puzzling finding was the poor performance delivered by the commercial CpAg-ELISA used in the present study, which was able to detect only a small fraction (16%) of the microscopy-positive samples.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies showing that neonatal calves are highly susceptible to Cryptosporidium infections because of their immature immune system and high exposure to manure or equipment contaminated with oocysts of the parasite (e.g. Foster and Smith, 2009;Murakoshi et al, 2013;Björkman et al, 2015). A puzzling finding was the poor performance delivered by the commercial CpAg-ELISA used in the present study, which was able to detect only a small fraction (16%) of the microscopy-positive samples.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the GP60 nucleotide sequences detected from the two different locations were identical to each other, and were classified as the IIaA15G2R1 subtype. Furthermore, previous analyses of the GP60 subtype of C. parvum from Gifu, Kobe, Hokkaido, and the most recent epidemiological study performed in the Ishikari district of Hokkaido also reported the occurrence of the IIaA15G2R1 subtype alone [14,17,37]. These findings suggest that C. parvum with the IIaA15G2R1 subtype is predominant in Japan.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, the nucleotide sequences obtained from nested polymerase chain reactions (PCRs) of the small subunit ribosomal RNA (SSUrRNA) and glycoprotein 60 (GP60) genes have been employed as tools for accurate species identification and subtyping analysis, respectively [9][10][11][12][13]. Although some epidemiological studies on C. parvum in Japan have been performed using these DNA markers [14][15][16][17], they did not characterize the C. parvum populations from more than one region of the country. Therefore, the aim of the present study was not only to obtain epidemiological information about C. parvum based on SSUrRNA and GP60 gene sequences, but also to compare the characteristics of this parasite in two different Japanese prefectures, southernmost Okinawa and northernmost Hokkaido.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was more difficult to identify a single causative agent of diarrhea in calves than it was in adult cows. Because our study did not include a diagnostic test for Cryptosporidium spp., one of the major diarrhea‐associated pathogens in calves in Japan , we cannot exclude the possibility that infection with Cryptosporidium spp. was responsible for the diarrhea in some of the calves for which no pathogen was detected.…”
Section: Frequency and Clinical Symptoms Of Bcv Bovine Rvb And Rvc mentioning
confidence: 99%